2021
DOI: 10.3390/vaccines9010063
|View full text |Cite
|
Sign up to set email alerts
|

HPV Vaccination Attitudes and Behaviors among General Practitioners in Italy

Abstract: This cross-sectional electronic online or telephone survey assessed the attitudes and behaviors regarding human papillomavirus (HPV) vaccination and the effect of different factors among a nationally representative random sample of 349 general practitioners (GPs) in Italy. A semi-structured interview was performed between September 2018 and October 2020. Almost all respondents considered the HPV vaccine safe with an overall mean value of 8.8, on a scale ranging from 1 to 10, and 59.9% and 32.6% believed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
4
6
0
1
Order By: Relevance
“…Indeed, having received information about COVID-19 vaccination from scientific journals was one of the most significant influential factors of the self-reported reason that it was important to have this vaccination for fear of getting the disease. This is consistent with previous studies also conducted in other countries that have shown that having received information from the scientific journals had a positive influence on the individual decision making regarding vaccination [29,[34][35][36][37][38][39][40][41][42]. There is clearly a need for HCWs, as part of this sample, to be able to develop competencies aimed to overall improve the vaccination uptake for them and for the general population in this geographic area.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, having received information about COVID-19 vaccination from scientific journals was one of the most significant influential factors of the self-reported reason that it was important to have this vaccination for fear of getting the disease. This is consistent with previous studies also conducted in other countries that have shown that having received information from the scientific journals had a positive influence on the individual decision making regarding vaccination [29,[34][35][36][37][38][39][40][41][42]. There is clearly a need for HCWs, as part of this sample, to be able to develop competencies aimed to overall improve the vaccination uptake for them and for the general population in this geographic area.…”
Section: Discussionsupporting
confidence: 91%
“…The trust of the sampled HCWs in this source of information, in particular scientific journals, has a strategic value in acquiring adequate and correct information and suggests that they must use these sources as a clue to adhere to vaccination recommendations to improve uptake of influenza vaccine in this high group at risk. The current findings should also be considered alongside existing scientific evidence from previous studies among HCWs showing that the use of these sources of information is known to be consistently and significantly associated with a higher level of vaccination knowledge, more positive attitudes, perceptions of the need to receive vaccines, and higher adherence to vaccination recommendations by governmental and health organizations [ 29 , 30 , 31 , 32 , 33 , 34 ]. The fact that about one-third of the respondents searched the Internet and media for information about vaccination is of concern since it is not easy to filter irrelevant or wrong information from these sources.…”
Section: Discussionmentioning
confidence: 61%
“…Among the limitations, it should certainly be pointed out that it could have been very useful to include, in parallel with the measurement of the vaccine recommendation, a measure of fear of the potential undesirable effects of vaccines [44]. The next studies, also in order to be able to compare the results, will certainly have to consider other variables already used in the literature [45].…”
Section: Discussionmentioning
confidence: 99%